Continuum of Academic Collaboration: Issues of Inconsistent Terminology in Multilingual Context - Leon, Cristo; Lipuma, James; Cabobianco, Marcos O.; Daizo, Maria B. (Journal of systemics, cybernetics and informatics, 2025)
This article investigates the challenges posed by inconsistent terminology in academic collaboration, particularly in multilingual contexts, focusing on Spanish and English. It begins by outlining the evolution of academic disciplines and the increasing need for collaborative research, providing foundational definitions that frame the discussion. The Continuum of Academic Collaboration (CAC) is introduced as a conceptual framework for categorizing different modes of collaboration. Through scholarly presentations and research discussions, the authors identified a significant gap in the translation and interpretation of key technical terms—especially those used to differentiate between multidisciplinary and interdisciplinary collaboration, such as the prefixes Co-, Cross-, and Across-. The findings indicate that inaccurate translations can lead to misinterpretations that undermine the conceptual integrity of these terms, as direct equivalents often fail to capture their nuanced meanings. A systematic literature review revealed limited clarity and a scarcity of research on these issues in Spanish-language publications. To address this gap, the authors interviewed esteemed experts whose insights underscore the need for further investigation into the multilingual translation of academic collaboration concepts, ultimately aiming to enhance transdisciplinary communication (TDC).